The contribution of Islamic banking operations to the financing of foreign trade - Ghouireg, Mohammed; Medaouakh, Madjda (The International tax journal, 2025)
Foreign trade holds substantial importance for all nations, with a country's economic strength often assessed by its export capacity and its ability to penetrate new markets through the exchange of goods and services in the form of exports and imports, aimed at generating mutual benefits. This requires the existence of reliable financing mechanisms for foreign trade operations. Banks, serving both as financial providers and intermediaries, play a crucial role by delivering the necessary funding to exporters and importers while facilitating the flow and collection of capital. In this context, Islamic banks contribute significantly to the facilitation of foreign trade operations by protecting the rights of both exporters and importers and ensuring that transactions align with international delivery terms as well as the principles of Shariah.